Urinary Tract Obstruction Secondary to Fungal Balls: A Systematic Review - Kenneth Keen Yip Chew; Maryaan Kas; Pascal Mancuso (Société Internationale d’Urologie Journal)
Objectives: To understand the clinical characteristics, risk factors, diagnosis, treatment, and outcomes of urinary tract obstruction caused by fungal balls. Materials and Methods: A comprehensive search was conducted across PubMed, Embase, and Medline following the PRISMA guidelines, including case reports and case series. Study quality and risk of bias were assessed using the Oxford Centre for Evidence-Based Medicine (CEBM) document. The systematic review process was aimed at gathering and synthesising all available research evidence on the topic. Results: We included 54 articles reporting on 57 patients, primarily males (61.4%) with a median age of 56 years. The most common presenting symptoms were flank pain (71.9%) and fevers (59.6%). All diagnoses were made on the presence of yeast in urine or intra-operative tissue cultures and the presence of obstruction on imaging. The most common pathogen isolated were those of the Candida species (61.5%) followed by Aspergillus (33.3%). Multimodal management was the mainstay approach with the use of systemic and local antifungal therapy in combination with surgical drainage of the obstruction. The mortality rate was around 12.3%. Conclusions: Management of renal or ureteral obstruction caused by fungal balls requires a multimodal and multidisciplinary approach, comprising systemic antifungal therapy, drainage procedures, and in some instances, surgical intervention. The growing prevalence of antifungal resistance and the high mortality potential of fungal uropathy necessitates ongoing research into the optimal diagnostic and treatment modalities for this condition.